SPIRITUALISING THE SECULAR: RELIGION AND ACCOUNTABILITY EVASION IN NIGERIA - Jacob Abur, Aondoaver; Flamboyant Martindales, Festus; Victor Amase, Terhemba (African Journal of Social and Behavioural Sciences, 2026)
In Nigeria, political elites increasingly employ a mechanism termed “spiritualising the secular” to evade accountability. By framing governance failures—such as corruption, economic instability, and insecurity—as spiritual issues or divine will, state actors successfully shift responsibility away from institutional mismanagement. Utilizing Postcolonialism and Strategic Rhetoric/Framing theories, this study analyzes political discourse, public statements, and policy justifications. It examines the correlation between religious rhetoric and major governance crises through historical analysis and specific case studies. The research identifies specific mechanisms of evasion, including divine punishment framing and state- sponsored religious rituals. This instrumentalization of faith serves to pacify public discontent and delegitimize dissent. The findings reveal a destructive cycle where spiritualisation erodes institutional trust, deepens ethno-religious polarization, and entrenches political impunity. To restore democratic accountability, the article proposes a multi-pronged approach: enhancing civic education to foster critical thinking, facilitating interfaith dialogue for inclusive governance, and implementing legal reforms to protect secular boundaries. Addressing this metaphysical reframing of state failure is essential for advancing transparent, performance-based governance and ensuring long-term socio-political stability in Nigeria.